ANALISIS PENGELOLAAN PERSEDIAAN PADA PT. DAUN BUAH KALTIM DI SAMARINDA - Heriyanto, Petronela Hangin, Elfreda A. Lau, (EKONOMIA, 2015)
The aim of research to determine the amount of brown that must be provided by the company for the foreseeable future. Basic theory used in this study include the Inventory Accounting understanding, purpose and function of inventory and record keeping and inventory valuation method. The data used is secondary data obtained from the object of research is PT. Daun Buah Kaltim.Formulation of the problem Is supply management Chocolate / cocoa on PT. Daun Buah Kaltim in Samarinda has done optimally. Inventory Management put forward the hypothesis that Chocolate / cocoa on PT. Daun Buah Kaltim not optimal. The analysis tool models Economic Order Quantity (EOQ), with the following procedure : 1). Calculate the optimal amount of inventory 2). Calculating the cost of storage per year 3). Calculate the total cost per year 4). The method used here is a comparative (comparison) where an order made the company the number of orders with EOQ model.Based on the calculation of EOQ (Economic Order Quantity) shows that the optimal inventory that occurred as much as 13 228 kg for the costs once the booking is Rp 250,000, - the booking fee per year is Rp 1.385 million, - the frequency of booking as much as five times a year, the number of supply each time booking as many as 13 228 kg. For storage costs known based on the analysis conducted is Rp 1.38894 million, - a year. It is the result of multiplying the average frequency multiplied by the storage cost in the form of a percentage set by the company, in this case the company set at 0.5% of the value of the goods. Brown price per kg is USD. 42,000, - the number of reservations once known as 13 228 kg. The total cost of Rp 2.77494 million, - The number is the results is booking fee plus the cost of storage.Based on the results of the calculation of the company should make a reservation as much as five times a year that is now done as much as seven times the number of bookings as much as 13 228 kg once the booking is do now as much as 6,100 kg. Total inventories as much as 13 228 kg is optimal inventory with a total cost of Rp 2.77494 million. for a period of a good booking is for 52 days of work per one booking. From the research that the hypothesis Brown inventory management conducted by PT. Daun Buah Kaltim in Samarinda reveived not optimal.